Online student engagement and entrepreneurial intention: Mediating role of individual entrepreneurial orientation - Wei-Loon Koe; Ramesh Krishnan; Najihah Hanisah Marmaya (AMH International, 2024)
Using new digital technology in education has become a reality everyone must accept with the development of Education 5.0. Moreover, online learning is no longer alien to most university students after the COVID-19 pandemic. Currently, the traditionally practical-focused entrepreneurship course is also available online. However, little extant literature has investigated student engagement in online learning, particularly for entrepreneurship courses. Therefore, this paper aimed to establish a new model to show how student engagement in online learning affected individual entrepreneurial orientation (IEO) and entrepreneurial intention (EI). This paper employed the online student engagement (OSE) model, the concept of IEO and the Theory of Planned Behavior (TPB) in developing the research model. The data were analyzed using partial least squared-structural equation modeling (PLS-SEM). The results indicated that IEO positively affected two elements of OSE, namely emotion and participation. A positive relationship was found between IEO and EI. It further found that IEO mediated the relationships between emotion and EI as well as between participation and EI. Therefore, it concluded that IEO was a crucial determinant of EI and it enhanced the relationship between OSE and EI. This paper produced both literature and practical outcomes. Literary, it produced a new model which explained the relationships among OSE, IEO and EI. Practically, it identified critical factors that higher education institutions could take into consideration in developing student entrepreneurs. It was also critical in supporting Malaysian governmental agendas that focused on developing competitive entrepreneurs, such as the Economic Transformation Program (ETP) and Malaysia Education Blueprint 2015-2025 (Higher Education).